Oncogenic signaling inhibits c-FLIPL expression and its non-apoptotic function during ECM-detachment - Matyas Abel Tsegaye; Jianping He; Kyle McGeehan; Ireland M. Murphy; Mati Nemera; Zachary T. Schafer (Scientific Reports, 2021)
Abstract Inhibition of programmed cell death pathways is frequently observed in cancer cells where it functions to facilitate tumor progression. However, some proteins involved in the regulation of cell death function dichotomously to both promote and inhibit cell death depending on the cellular context. As such, understanding how cell death proteins are regulated in a context-dependent fashion in cancer cells is of utmost importance. We have uncovered evidence that cellular FLICE-like Inhibitory Protein (c-FLIP), a well-known anti-apoptotic protein, is often downregulated in tumor tissue when compared to adjacent normal tissue. These data argue that c-FLIP may have activity distinct from its canonical role in antagonizing cell death. Interestingly, we have discovered that detachment from extracellular matrix (ECM) serves as a signal to elevate c-FLIP transcription and that oncogenic signaling blocks ECM-detachment-induced c-FLIP elevation. In addition, our data reveal that downregulation of c-FLIP promotes luminal filling in mammary acini and that c-FLIP overexpression in cancer cells inhibits colony formation in cells exposed to ECM-detachment. Taken together, our study reveals an unexpected, non-apoptotic role for c-FLIP during ECM-detachment and raises the possibility that c-FLIP may have context-dependent roles during tumorigenesis.